2016
DOI: 10.1002/lt.24436
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic machine perfusion reduces bile duct injury and improves biliary epithelial function in rat donor livers

Abstract: Bile duct injury may occur during liver procurement and transplantation, especially in livers from donation after circulatory death (DCD) donors. Normothermic machine perfusion (NMP) has been shown to reduce hepatic injury compared to static cold storage (SCS). However, it is unknown whether NMP provides better preservation of bile ducts. The aim of this study was to determine the impact of NMP on bile duct preservation in both DCD and non-DCD livers. DCD and non-DCD livers obtained from Lewis rats were preser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 39 publications
0
58
0
Order By: Relevance
“…This has led various learned societies to re-define ARF as acute kidney injury (AKI), incorporating even small changes in serum creatinine either in absolute or percentage terms in the diagnostic criteria [4][5][6]. The degree of AKI severity is also defined by stages [4][5][6]. The most commonly reported classification used to diagnose AKI is that of the Acute Kidney Injury Network (AKIN), which set forth specific serum creatinine and urine output changes to define stages of AKI, without setting a fixed serum creatinine level in its diagnostic criteria [5].…”
Section: Supplementary Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This has led various learned societies to re-define ARF as acute kidney injury (AKI), incorporating even small changes in serum creatinine either in absolute or percentage terms in the diagnostic criteria [4][5][6]. The degree of AKI severity is also defined by stages [4][5][6]. The most commonly reported classification used to diagnose AKI is that of the Acute Kidney Injury Network (AKIN), which set forth specific serum creatinine and urine output changes to define stages of AKI, without setting a fixed serum creatinine level in its diagnostic criteria [5].…”
Section: Supplementary Datamentioning
confidence: 99%
“…More recently, it has been recognized in non-cirrhotic patients that smaller increases in serum creatinine also have a negative impact on survival [3]. This has led various learned societies to re-define ARF as acute kidney injury (AKI), incorporating even small changes in serum creatinine either in absolute or percentage terms in the diagnostic criteria [4][5][6]. The degree of AKI severity is also defined by stages [4][5][6].…”
Section: Supplementary Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In normothermic machine perfusion, the liver is kept viable ex situ by perfusion with warm oxygenated blood. 395,399 Mild hypothermia may lower the rate of DGF in kidney transplantation recipients, especially if high-risk donors, such as donors with a high KDPI, are used. 367 In a study of hypothermic machine perfusion in 31 adults receiving livers from donors with a high KDPI, EAD was lower in this group (19%) compared to the static cold storage control group (30%), with significantly less biliary complications (4 vs 13; P = 0.016).…”
Section: Donor Managementmentioning
confidence: 99%
“…A recent study in rats reported that normothermic machine perfusion provided better preservation of bile duct epithelial cell function and morphology in both DCD, and non-DCD livers (after 3 hours, followed by 2 hours ex vivo reperfusion), compared with static cold storage. 399 Another study using continuous normothermic machine perfusion from procurement to transplantation in pig liver transplants resulted in good posttransplantation survival, even after 20 hours of warm preservation. 400 The use of continuous perfusion is thought to be necessary because normothermic Considerations for managing EAD and nonanastomotic BS in liver transplantation 32,384,387,388,392,395,[397][398][399][400][401][402] …”
Section: Donor Managementmentioning
confidence: 99%